Mechanistic insight into the dramatic improvement of probucol dissolution in neutral solutions by solid dispersion in Eudragit E PO with saccharin. (14th August 2015) - Higashi, Kenjirou; Seo, Atsunori; Egami, Kiichi; Otsuka, Naoya; Limwikrant, Waree; Yamamoto, Keiji; Moribe, Kunikazu
Abstract: Objectives: Solid dispersion using Eudragit E PO (EPO) improves the dissolution of poorly water-soluble drugs in acidic solutions; however, the dissolution extremely decreases in neutral solutions. In this report, ternary solid dispersions containing probucol (PBC), EPO, and saccharin (SAC) were prepared to enable high drug dissolution at neutral pH. Methods: Cryogenic-grinding was used to obtain ternary solid dispersions. Dissolution tests at neutral pH values were conducted to confirm the usefulness of the cryogenic-ground mixture (cryo-GM). The molecular state of each component and intermolecular interactions in the ternary cryo-GM were evaluated using powder X-ray diffraction (PXRD) and 13 C solid-state NMR including spin-lattice relaxation time evaluation. Key findings: PBC dispersed in ternary cryo-GM had an improved dissolution in neutral solutions. PBC and SAC were in amorphous states in EPO polymer matrices. The weak hydrophobic interaction between PBC and EPO and the ionic bond or hydrogen bond between EPO and SAC were demonstrated. These two molecular interactions improved the dissolution of PBC in neutral solutions. Conclusion: Preparation of ternary solid dispersion is a potential method of improving drug solubility and absorption.